¿Prociclicidad en Basilea II?: un análisis de los requerimientos de capital en los créditos comerciales de la banca múltiple peruana - Trelles C., Alejandro Jaime (2009)
The Basel committee has proposed a New Capital Accord (NCA) which introduces a new methodology to calculate the minimum capital requirements considering that in the new accord, the capital requirements are more sensitive to risk. The loans offered by financial institutions and the risk measurement, in particular, show a very cyclical behavior. This means that both variables are strongly related with the rest of the macroeconomic variables through time. In this way, the risks that are perceived by the financial institutions are likely to be reduced strongly when we are through an expansionary phase, whereas in a recession, they tend to increase. This is the main reason why a new regulation that would make capital requirements more sensitive to risk measurement, which already has a cyclical component, could introduce an additional pro-cyclical factor which in time could be dangerous because it is likely to exacerbate the economic cycles by increasing the length and magnitude of the economic phase. Consequently, this might end up generating a considerable volatility (instability) within the financial system. Therefore, by incorporating the NCA to Peru’s financial system, it is our goal to assess whether the corporate loans from the Peruvian banking system will carry and additional degree of pro-cyclicality to the banking system given that they would be more sensitive to risk measurement under the new accord. Under four different models, we found that the probability of default of the corporate loans is very sensitive to the economic cycle. Consequently, we found that the evolution of the capital requirements of the corporate loans has a high volatility, which might also increase the length of the economic cycle generating in that way further instability within the financial system as well as within the economy. Finally, we performed several stress tests on the GDP growth and as a result we found out that the effect on the corporate loan’s probability of default was significant and that it might increase up to 85%. These findings allow us to provide a series of measures to reduce the volatility of the capital requirements.